2021
DOI: 10.1186/s12889-021-10174-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to using HIV pre-exposure prophylaxis (PrEP) and sexual behaviour after stopping PrEP: a cross-sectional study in Germany

Abstract: Background Persistence of individuals at risk of HIV with Pre-Exposure Prophylaxis (PrEP) is critical for its impact on the HIV epidemic. We analysed factors associated with stopping PrEP, barriers that may deter people from continuing PrEP and investigated sexual behaviour after stopping PrEP. Methods Current and former PrEP users in Germany were recruited to complete an anonymous online survey on PrEP use and sexual behaviour. Participants were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 36 publications
1
30
0
13
Order By: Relevance
“…As a retrospective study, we are also aware that the data collected might be affected by an information bias; however we believe this model of care could be translatable in other healthcare contexts with similar patient cohorts. PrEP fatigue, leading to sub-optimal PrEP adherence and subsequently discontinuation is an increasingly documented phenomenon [ 20 ]. This could impact in the future frequency of clinically relevant resistance, as numbers of individuals exposed to PrEP increase.…”
Section: Discussionmentioning
confidence: 99%
“…As a retrospective study, we are also aware that the data collected might be affected by an information bias; however we believe this model of care could be translatable in other healthcare contexts with similar patient cohorts. PrEP fatigue, leading to sub-optimal PrEP adherence and subsequently discontinuation is an increasingly documented phenomenon [ 20 ]. This could impact in the future frequency of clinically relevant resistance, as numbers of individuals exposed to PrEP increase.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Patients who discontinue PrEP care are more likely to be younger and predominantly choose event-based PrEP. 18 , 19 Potential reasons for discontinuing PrEP care are a lower perceived risk for HIV, fear of side effects or experiencing logistical and financial barriers. 17 , 19 …”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 Potential reasons for discontinuing PrEP care are a lower perceived risk for HIV, fear of side effects or experiencing logistical and financial barriers. 17 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies consistently found that younger respondents displayed greater willingness to take PrEP [ 61 , 64 66 ]. However, mixed results have been reported in studies measuring age in association with actual use of PrEP: Several studies reported that PrEP users were more likely to be of older age [ 67 , 68 ] while other studies reported a greater likelihood of usage among the younger MSM [ 69 , 70 ]. For its research purpose, which investigates the willingness to take PrEP, the current study will examine age in accordance with previous findings indicating higher willingness to take PrEP among younger MSM.…”
Section: Towards a Multidisciplinary Understanding Of Hiv-preventionmentioning
confidence: 99%
“…Correspondingly, findings focusing on PrEP uptake show that financial means play an important part. For instance, studies conducted in Germany when PrEP was already accessible through the healthcare system for monthly payment of 50–70 EUR and without routinely medical examinations covered by statutory insurances showed that MSM rather purchased PrEP through informal and cheaper sources than the legal market due to unaffordable costs via official providers [ 17 , 69 ], supporting the notion of higher willingness among MSM with lower income. Accordingly, we expect a negative association between income and willingness (hypothesis 4d).…”
Section: Towards a Multidisciplinary Understanding Of Hiv-preventionmentioning
confidence: 99%